Multiphase Transformer Modelling using Finite Element Method - Nor Azizah Mohd Yusoff; Kasrul Abdul Karim; Sharin Ab Ghani; Tole Sutikno; Auzani Jidin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In the year of 1970 saw the starting invention of the five-phase motor as the milestone in advanced electric motor. Through the years, there are many researchers, which passionately worked towards developing for multiphase drive system. They developed a static transformation system to obtain a multiphase supply from the available three-phase supply. This idea gives an influence for further development in electric machines as an example; an efficient solution for bulk power transfer. This paper highlighted the detail descriptions that lead to five-phase supply with fixed voltage and frequency by using Finite-Element Method (FEM). Identifying of specification on a real transformer had been done before applied into software modeling. Therefore, Finite-Element Method provides clearly understandable in terms of visualize the geometry modeling, connection scheme and output waveform.